Reforming regional government system and social well-being of local population: territorial aspects - S. N. Kalyugina (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The relevance of the topic is justified by the need to summarize the interim results of the pilot project on the formation of a single-level system of local self-government and its impact on the socio-economic development of territories in the region under study.Goal. The paper aims to study the nature of the impact of transformations on the socio-economic development of territories and the attitude of the population to the creation of municipal and urban districts.Materials and methods. In order to analyze the approaches to the organization of local self-government in Russia and summarize the interim results of their implementation, the research used general scientific and private-scientific research methods, methods of logical-methodological, structural-functional and system analysis. The method of pilot sociological research was used to study the attitude of the population and municipal servants to the results of the administrative-territorial reform.Results and discussion. In the course of the work, it was found that the transformations carried out in the Stavropol Krai have both positive and negative effects on the socio-economic development of territories and the social well-being of the population. In this regard, the process of improving the activities of regional and municipal authorities for further transition to a single-level system of local self-government is of particular importance. In this regard, the process of improving the activities of regional and municipal authorities on further transition to a single-tier system of local self-government is of particular importance.Conclusion. According to the results of the study, it can be concluded that in order to improve the social well-being of the population, regional and municipal authorities of the pilot regions need to develop and implement a set of measures to mitigate and eliminate the negative consequences of the ongoing administrative-territorial reform.